The Effect of White Turmeric Extract (Curcuma mangga Val) in Commercial Feed on the Growth of Tilapia (Oreochromis niloticus) - Ulaan, Magdalin; Mose, Numisye I; Indriani, Yeni; Saselah, Jetti T; Manganang, Yessi A. P. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Indonesia's high biodiversity has great potential to be developed in various fields, including fisheries. To support sustainable and environmentally friendly aquaculture activities, the utilization of local natural resources is one of the keys to increasing the competitiveness of the national fisheries sector amid global challenges related to food security and the environment. One alternative source that can be used as a natural feed supplement in fish farming is from the Curcuma genus, such as white turmeric (Curcuma mangga Val). Therefore, the purpose of this study was to determine the effectiveness of white turmeric extract (Curcuma mangga Val) on the growth of tilapia. The research design used was a completely randomized design consisting of 3 treatments and 3 replicates, namely: Treatment A (feed without turmeric extract), Treatment B (feed added with 5 ml of white turmeric extract), and Treatment C (feed added with 10 ml of white turmeric extract). Feed was administered three times daily at a dose of 5% of body weight. The results showed that the addition of white turmeric extract (Curcuma mangga Val.) significantly increased the growth of Nile tilapia (Oreochromis niloticus). The most effective treatment dose was Treatment C (10 ml/kg of feed), which resulted in an absolute average increase of 8.99 g in weight and 2.67 cm in length.